STRATEGI PELAYANAN ADMINISTRASI KEPENDUDUKAN DALAM MENINGKATKAN KEPUASAN MASYARAKAT - Fadian Putry; Nurma Yeni; Reza Kusuma Wardani (YUDABBIRU JURNAL ADMINISTRASI NEGARA, 2023)
Various kinds of problems in the implementation of public services cannot be avoided, in the eyes of the public, the government is still considered unable to provide good public services so that they feel dissatisfied with the services they receive. For this reason, it is necessary to refresh the service strategy so that government services become better, especially in population administration. This study uses a literature study research method with data collection techniques based on a collection of previous studies to answer questions related to Population Administration Service Strategies in Increasing Community Satisfaction. The results of this study indicate that population administration services must continue to develop and improve their competence both physically (infrastructure) and non-physically (employee performance) in order to achieve the goal of good service to the community. So, a strategy is needed to achieve the implementation of these services, guided by 6 dimensions of achieving optimal quality of public services including; Reability, Responsiveness, Assurance, Empathy, Tangibles and Access.